Strategi Optimalisasi Google My Business (GMB) dalam Meningkatkan Daya Saing Digital UMKM di Kelurahan Kampung Baru Kota Medan - Iskandar, Ihsan (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The rapid advancement of information technology has driven micro, small, and medium enterprises (MSMEs) to adapt digital marketing strategies to remain competitive. This study analyzes the impact of Google My Business (GMB) in enhancing the online marketing performance of MSMEs in Kelurahan Kampung Baru, Medan City. The research involved direct mentoring for 15 selected MSMEs to register and optimize their GMB profiles. The method included observational analysis through GMB analytics to measure visibility improvements. Findings indicate that GMB significantly increases business visibility, with the highest profile view reaching 137 and the lowest at 5 views within a week. GMB also facilitates easier customer access to business information, contributing to broader market reach and improved sales potential. This study emphasizes the strategic role of GMB in empowering MSMEs to adapt to the digital era and expand their market penetration.